Mitragyna speciosa (Kratom) poisoning: Findings from ten cases. (15th March 2023) - Peran, David; Stern, Michael; Cernohorsky, Petr; Sykora, Roman; Popela, Stanislav; Duska, Frantisek
Abstract: Kratom is a mixture of compounds that are present in the leaves of the tropical tree Mitragyna speciosa. It is used as a psychoactive agent with both opiate and stimulant-like effects. In this case series we describe the signs, symptoms, and the management of kratom overdose in the prehospital setting and in intensive care. We retrospectively searched for cases in the Czech Republic. Over 36 months we found 10 cases of kratom poisoning, which healthcare records were analyzed and reported as per CARE guidelines. The dominant symptoms in our series were neurological and included quantitative (n = 9) or qualitative (n = 4) disorder of consciousness. Signs and symptoms of vegetative instability [hypertension (n = 3) and tachycardia (n = 3) vs. bradycardia/cardiac arrest (n = 2), mydriasis (n = 2) vs. miosis (n = 3)] were noticed. Prompt response to naloxone in two cases and lack of response in one patient were observed. All patients survived and the effect of intoxication wore off within two days. Kratom overdose toxidrome is variable and, in keeping with its receptor physiology, consists of signs and symptoms of opioid-like overdose, sympathetic overactivation and serotonin-like syndrome. Naloxone can help to avoid intubation in some cases. Graphical abstract: Image 1 Highlights: Kratom is a relatively new and rapidly spreading plant-based legal high in Europe. Overdose presents with impaired consciousness. Overdose presents with opioid-like symptoms, sympathetic and serotonin syndromes. There is no diagnostic test for the use at bedside. Naloxone can be tried to avoid the need of intubation.